AKTIVITAS IMUNODULATOR DARI JAWER KOTOK (Coleus scutellariodes (L) Benth) - Adinda Putri Sabrina; Evi Tania; Nurhalifah Nurhalifah; Santika Citra Veronita; Shella Imka Puji; Siti Nuryamah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Coleus scutellariodes (L), commonly known as Jawer kotok plant, is a medicinal plant that has many properties, one of which is as an immunodulator and some of its pharmacological activities. The leaves of this plant have various uses in traditional medicine for a number of diseases. Lots of substances contained in this plant such as flavonoids, saponins, tannins, alkaloids, steroids. One of the substances contained in jawer kotok leaves has efficacy as an immunodulator, namely flavonoids. Several studies have demonstrated the pharmacological exploration of Coleus scutellariodes (L) as an infectious disease (Tuberculosis), Anti-Inflammatory (vulvovaginal candidiasis), Antipyretic, Antioxidant-Active, Anti-diabetic, Anti-histamine, Anti-anthelmic. In this journal review, a comprehensive study focused on knowledge of plant functions as immunodulators, pharmacological activities and phytochemical studies of the jawer kotok plant Coleus scutellariodes (L).Keywords: Guides, instructions, author’s kit, conference publications.